Policy‐Maker of Last Resort? Drivers of Discretion at the European Central Bank - Shawn Donnelly (Politics and Governance)
Under what conditions does the ECB become the policy-maker of last resort? This article surveys five incidences in which the ECB created its own rules or exercised discretion beyond the effective control of political principals. ECB rule-making took place where the Bank had an initial legal mandate to be present in the policy space, where it could exploit unique institutional interfaces with the banking community and Economic and Monetary Union system, where it had advantages in expertise and information, and where the Council either fully supported the ECB to design new powers, or was divided on whether to retrench ECB freedom. The article examines discretion in macroeconomic policy instruments, capital requirements for banks, including choices that have industrial policy (targeted sectoral) effects, the design of the digital euro, and ECB efforts to force the migration of UK-based financial services to the EU.